2014
DOI: 10.21916/mlr.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

Examining the completeness of occupational injury and illness data: an update on current research

Abstract: Occupational health surveillance data are key to effective intervention. However, the US Bureau of Labor Statistics survey significantly underestimates the incidence of workrelated injuries and illnesses. Researchers supplement these statistics with data from other systems not designed for surveillance. The authors apply the filter model of Webb et al. to underreporting by the Bureau of Labor Statistics, workers' compensation wage-replacement documents, physician reporting systems, and medical records of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Because OSHA recordkeeping guidelines do not apply to all employers, SOII does not include private household workers, self‐employed individuals, farm employers with fewer than 11 employees, and employees of the federal government and United States Postal Service. The likelihood of a case being captured in SOII has been associated with the type of injury or illness [Wiatrowski, ], the duration from injury or illness onset to reporting, ability to determine work‐relatedness [Nestoriak and Pierce, ], and compliance with OSHA recordkeeping guidelines [Wuellner and Bonauto, ].…”
Section: Introductionmentioning
confidence: 99%
“…Because OSHA recordkeeping guidelines do not apply to all employers, SOII does not include private household workers, self‐employed individuals, farm employers with fewer than 11 employees, and employees of the federal government and United States Postal Service. The likelihood of a case being captured in SOII has been associated with the type of injury or illness [Wiatrowski, ], the duration from injury or illness onset to reporting, ability to determine work‐relatedness [Nestoriak and Pierce, ], and compliance with OSHA recordkeeping guidelines [Wuellner and Bonauto, ].…”
Section: Introductionmentioning
confidence: 99%
“…The United States Congress passed the Occupational Safety and Health Act in 1970 with the aim of ensuring employers provide employees a harmless working environment. According to this Act, the United States Department of Labor established the Occupational Safety and Health Administration with the aim of preventing work-related injuries, illnesses, and occupational fatality by issuing and enforcing standards for workplace safety and health at the federal level [3] .…”
Section: The United Statesmentioning
confidence: 99%
“…BLS used the funding to build on existing research by conducting in‐depth assessments of the quality of SOII data [Wiatrowski, ]. BLS partnered with several state agencies and one contractor to conduct studies that involved: (i) matching data from SOII and workers' compensation; (ii) assessing the feasibility of using multiple data sources, such as SOII, workers' compensation records, and hospital emergency room records to identify cases of carpal tunnel syndrome and amputations; and (iii) interviewing employers about their injury and illness recordkeeping practices for identifying and recording cases on their OSHA logs and workers' compensation claims [Wiatrowski, ]. Findings have suggested that employer recordkeeping issues may be more problematic with multi‐establishment companies and for certain types of injuries/illnesses that are more difficult to relate to work (e.g., hearing loss), and that some cases may be missed due to the timing of the survey [Ruser, ].…”
Section: Introductionmentioning
confidence: 99%